The presence of stress and leisure sports in the life of today’s people - Kinczel, Antónia (International Journal of Engineering and Management Sciences, 2020)
Today’s people are extremely busy with a lot of things, such as work, family, learning, so they try to spend their free time with activities that promote them in relaxation, reassurance, recreation. It can be said that the people of today’s world are burdened, more stressed and nervous, trying to do the best they can to live properly. A lot of people have a hard time communicating, community life. There are a lot of people who are forced to work from home, as projects and weeks’ deadlines don’t wait. Besides, there are many things to be done, children need to be dealt with, you have to have fun, you have to pay attention to health, you have to run a household, etc., so there is little time for people to do what they really love. In my research, I assessed the leisure habits of the inhabitants of Romania and Hungary, but their attitude to active reclamation activities (N=273) was their activity in sport. The results show that passive leisure activities (watching TV, reading, listening to music, internet) are still the most popular among people, although most of us do sedentary work. People who play sports in their spare time felt more refreshed, and they had a better mood, more positive. The sports that people can play outdoors and in parks come to the fore.